Proceedings of the 26th ACM Conference on Hypertext &Amp; Social Media - HT '15 2015
DOI: 10.1145/2700171.2791036
|View full text |Cite
|
Sign up to set email alerts
|

First Women, Second Sex

Abstract: Contributing to the writing of history has never been as easy as it is today. Anyone with access to the Web is able to play a part on Wikipedia, an open and free encyclopedia, and arguably one of the primary sources of knowledge on the Web. In this paper, we study gender bias in Wikipedia in terms of how women and men are characterized in their biographies. To do so, we analyze biographical content in three aspects: meta-data, language, and network structure. Our results show that, indeed, there are difference… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(31 citation statements)
references
References 37 publications
0
29
0
2
Order By: Relevance
“…Wagner et al [48] present a method for assessing gender bias on Wikipedia. Gender bias in Wikipedia is also studied by Graells-Garrido et al [18]. Magno and Weber [33] study gender inequality through user participation in two online social networks, Twitter and Google+, finding, for example, that the gap between the number of users correlates with the gender gap index, i.e., countries with more men than women online are countries with higher gender difference.…”
Section: Related Workmentioning
confidence: 96%
“…Wagner et al [48] present a method for assessing gender bias on Wikipedia. Gender bias in Wikipedia is also studied by Graells-Garrido et al [18]. Magno and Weber [33] study gender inequality through user participation in two online social networks, Twitter and Google+, finding, for example, that the gap between the number of users correlates with the gender gap index, i.e., countries with more men than women online are countries with higher gender difference.…”
Section: Related Workmentioning
confidence: 96%
“…Biographies of women are less well-developed and male editors are less likely to edit women's biographies (Reagle & Rhue, 2011). Studies also have found that the use of language varies between biographies of men and women (Graells-Garrido, Lalmas, & Menczer, 2015;Wagner, Graells-Garrido, Garcia, & Menczer, 2016). Wagner et al (2016) determined that articles on women were more likely to include gendered words like "women," "female," and "lady" compared with articles about men that rarely use gendered words such as "man," "male," or "gentleman."…”
Section: Women and Wikipediamentioning
confidence: 99%
“…Then, the statistical significance of the difference between distributions of image groups were tested using chi-square independence tests with Monte Carlo p-value simulations [22]. 11 We also explored how distribution of image categories would look like if one restricts professions to those with more than 70% men or women, respectively.…”
Section: Images Analysismentioning
confidence: 99%
“…For example, romantic relationships and family-related issues are much more frequently discussed about women than men. In [11,28,29] differences between descriptions of male and female biographies in terms of network structure, topical focus, structural properties and language were researched. Thus, several studies suggest that gender bias on Wikipedia can be assessed using articles with biographies.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation